Contrast Media in Time-Resolved MRA at 3T: A Systematic Quantitative and Qualitative Analysis of Concentration and Dose Effects on Image Parameters in Minipigs - Hadizadeh, Dariusch Reza; Keil, Vera Catharina; Jost, Gregor; Pietsch, Hubertus; Weibrecht, Martin; Marx, Christian; Willinek, Winfried (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2018)
Purpose Quantitative and qualitative analysis of gadopentetate dimeglumine (GD) versus standard-dose (sGb) and half-dose (hGb) gadobutrol in thoracoabdominal time-resolved contrast-enhanced magnetic resonance angiography (4D-MRA) with dynamic computed tomography (dCT) as the quantitative reference in minipigs.Materials and Methods 7 anesthetized Goettingen minipigs received thoracoabdominal dCT (0.37 s rotation time) and transverse 4D-MRA (0.3 s/dynamic frame;) using sGb and hGb. 8 other minipigs received coronal 4D-MRA (1.3 s/dynamic frame; sGb, hGb, SGD). dCT attenuation levels were converted into absolute gadolinium concentrations and compared to 4D-MRA peak signal intensities (SI). Bolus lengths were quantified by full width at half maximum (FWHM) measurements. After this comparison of dose effects on SI in transverse 4D-MRA, coronal 4D-MRAs were analyzed regarding both quantitative and qualitative parameters.Results In dCT (transverse 4D-MRA) hGb showed 39.0 % (14.5 %) lower arterial peak gadolinium concentrations (peak SIs) and 20.6 % (33.8 %) shorter FWHM compared to sGb. The difference was due to peak plateaus or reversals in 4D-MRA in 5/7 animals. While sGb led to the highest peak SIs, image quality ratings of arteries were rated similarly high with all contrast agent protocols despite a slightly higher SI with sGb. In contrast, venous peak SIs and image quality ratings were significantly higher when using sGb.Conclusion Peak Gd concentrations and 4D-MRA peak SIs are highest with sGB. These differences are most evident in the venous phase leading to superior image quality in multi-phase 4D-MRA.Key Points: Citation Format
Keywords: contrast agents; gadobutrol; experimental animal model; magnetic resonance angiography; gadopentetate dimeglumine